2020
DOI: 10.3233/wor-203205
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress and physiological and perceptual strains of date harvesting workers in palm groves in Jiroft

Abstract: BACKGROUND: Outdoor workers are exposed to heat caused by atmospheric conditions and solar radiation. More specifically, those working in palm groves are more in danger of heat stresses since they harvest their crops in hot seasons. OBJECTIVE: This study was aimed at investigating heat stresses and strains in date harvesting workers in groves around Jiroft, Southeastern Iran. METHODS: This study was a descriptive-analytical one of cross-sectional type. In this study, three environmental indices including Wet B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Five studies identified a strong association between HRI and hot environmental conditions as measured by WBGT ( Table 3 ) ( 72 , 75 , 84 , 85 , 87 ). Vega-Arroyo et al ( 75 ) reported that WBGT was associated with higher core body temperatures (β: 0.03, 95% CI: 0.017–0.05) among migrant farmworkers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies identified a strong association between HRI and hot environmental conditions as measured by WBGT ( Table 3 ) ( 72 , 75 , 84 , 85 , 87 ). Vega-Arroyo et al ( 75 ) reported that WBGT was associated with higher core body temperatures (β: 0.03, 95% CI: 0.017–0.05) among migrant farmworkers.…”
Section: Resultsmentioning
confidence: 99%
“…The most common heat-related health outcome assessed was HRI (n = 57; 62%). Twenty-seven out of 57 of these studies relied on selfreported HRI symptoms (25,27,30,(40)(41)(42), while 21 measured various physiological parameters such as core body temperature, skin temperature, heart rate, blood pressure, changes in body weight, or urine specific gravity (61,68,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Another commonly assessed heat-related health outcome was kidney disease (n = 28; 30%).…”
Section: Descriptive Characteristics Of Included Studiesmentioning
confidence: 99%
“…En el contexto laboral el concepto de estrés térmico abarca la suma total de calor al que se encuentran expuestos los trabajadores, siendo esta exposición el resultado de una interacción entre las condiciones ambientales presentes en su lugar de trabajo, el nivel de actividad física desempeñado y la indumentaria utilizada. La evaluación del estrés térmico implica considerar diversos factores, entre ellos la temperatura ambiental, radiación, velocidad del aire, humedad relativa, así como las actividades del trabajador y las propiedades de la ropa utilizada, incluyendo su emisividad y capacidad de radiación (Habib et al, 2021;García et al, 2015;Mohammadian et al, 2020).…”
Section: Introductionunclassified
“…Many other factors are elevating testicular temperature and they can be grouped according to habits, lifestyles ( 7 ; 19 ), occupational factors (i.e. prolonged exposure to high temperatures) ( 20 ; 21 ), and climate change ( 22 ). The association between the effect of high ambient temperature on human sperm parameters has also been investigated, but these results are indecisive and controversial.…”
Section: Introductionmentioning
confidence: 99%